The protective effects of momordica charantia fruit extractin methotrexate induced liver damage in rats - ÖZBEYLİ, DİLEK; KAYA, ÖZLEM TUĞÇE (My University, 2022)
BACKGROUND/AIMS: Methotrexate (MTX), a cytotoxic therapeutic agent, is used for the cure of malignancies and rheumatologic disorders. However, the significant side effects of MTX limits its use. In this study, we aim to assess the hepatoprotective properties of Momordica charantia (MC) against MTX-induced liver damaged in rats. MATERIALS AND METHODS: Following one dose of MTX (20 mg/kg), the rats were given either distilled water or MC extract (300 mg/kg, po) for 5 days. After the dissection of the rats, the liver was removed to analyse tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β), transforming growth factor β (TGF-β) and 8-hydroxy-2’-deoxy-guanosine (8-OhdG) levels and superoxide dismutase (SOD), catalase (CAT), and caspase-3 activities. The tissues were also examined histopathologically. RESULTS: The hepatic TNF-α, IL-1β, TGF-β, 8-OhdG levels, and Caspase-3 activity in the MTX group were found to be significantly increased compared to the control group. However, MC extract was able to significantly decrease TNF-α, TGF-β, 8-OhdG levels, and Caspase-3 activity. Also, both the SOD and CAT activity of the MTX group decreased compared to the control group. Although only the SOD levels elevated significantly with MC treatment, the SOD and CAT activities of the MC treated group were similar to the control group. Supporting these biochemical parameters, MTX-induced histologic alterations in the liver were also ameliorated via MC treatment. CONCLUSION: Our results demonstrated that MC has a protective role against MTX-induced hepatic tissue injury by reducing apoptosis, oxidative damage, and the expression of pro-inflammatory cytokines.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)